Is epistemic orientation the chicken or the egg in professional development for knowledge generation approaches?. (August 2022) - Lammert, Catherine; Suh, Jee Kyung; Hand, Brian; Fulmer, Gavin
Abstract: Professional development has been marginally successful at encouraging the knowledge generation approaches promoted in international education policy. To explore whether increased attention to teachers' epistemic orientations might suggest necessary innovations to existing professional development routines, an explanatory sequential mixed-methods analysis was conducted inside a three-year professional development program for in-service elementary science teachers in two U.S. states. Findings suggest that teachers' epistemic orientations influenced their willingness to engage with knowledge generation approaches, challenge teacher educators' claims, and implement knowledge generation approaches in their classrooms, indicating an interrelated relationship between these factors. Implications for professional development design and recruitment are discussed. Highlights: Epistemic orientation influences teachers' willingness to consider utilizing knowledge generation approaches. Following professional development, teachers' epistemic orientations and their teaching practices showed alignment. Teachers oriented toward knowledge replication did not often create generative learning environments. Teachers oriented toward knowledge generation often created generative learning environments. An interrelated relationship exists between epistemic orientation, professional development, and classroom practice.